A MULTI-PERIOD GROUP TECHNOLOGY METHOD FOR DYNAMIC CELLULAR MANUFACTURING SYSTEMS - Padayachee, Jared; Bright, Glen (The South African Journal of Industrial Engineering, 2016)
A dynamic cellular manufacturing system is a system where cell configurations change in order to respond to changing production requirements. This paper proposes methods for multi-period cell and part family formation. The method of fuzzy C-means clustering is used for part family formation while balancing the part load between cells in each period; a genetic algorithm is presented to solve the model. An integer programming model is presented for multi-period cell formation with the objective of determining an optimal trade-off between reconfiguration cost and the cost of deficit capacity.